2012
DOI: 10.1364/oe.20.022118
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous temperature, mixture fraction and velocity imaging in turbulent flows using thermographic phosphor tracer particles

Abstract: This paper presents an optical diagnostic technique based on seeded thermographic phosphor particles, which allows the simultaneous two-dimensional measurement of gas temperature, velocity and mixture fraction in turbulent flows. The particle Mie scattering signal is recorded to determine the velocity using a conventional PIV approach and the phosphorescence emission is detected to determine the tracer temperature using a two-color method. Theoretical models presented in this work show that the temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
89
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 38 publications
10
89
1
Order By: Relevance
“…From repeated measurement sequences, the maximum deviation of the mean measured temperatures to the flow temperature indicated by a thermocouple positioned in the measurement plane was only 5 K. This level of temperature precision is comparable with that achieved in a previous study using a low speed measurement system based on interline transfer CCD cameras and low repetition rate flashlamp pumped solid-state lasers [11]. BAM:Eu saturates at fluences around 2 mJ/cm 2 [11], so the phosphorescence emission intensity is comparable for the two cases as saturation can also be achieved with the high-speed 355 nm laser. The readout noise of CMOS cameras is larger than that of the CCD cameras used in [11].…”
Section: Accuracy and Precision Of High-speed Phosphor Thermometrysupporting
confidence: 81%
See 3 more Smart Citations
“…From repeated measurement sequences, the maximum deviation of the mean measured temperatures to the flow temperature indicated by a thermocouple positioned in the measurement plane was only 5 K. This level of temperature precision is comparable with that achieved in a previous study using a low speed measurement system based on interline transfer CCD cameras and low repetition rate flashlamp pumped solid-state lasers [11]. BAM:Eu saturates at fluences around 2 mJ/cm 2 [11], so the phosphorescence emission intensity is comparable for the two cases as saturation can also be achieved with the high-speed 355 nm laser. The readout noise of CMOS cameras is larger than that of the CCD cameras used in [11].…”
Section: Accuracy and Precision Of High-speed Phosphor Thermometrysupporting
confidence: 81%
“…BAM:Eu saturates at fluences around 2 mJ/cm 2 [11], so the phosphorescence emission intensity is comparable for the two cases as saturation can also be achieved with the high-speed 355 nm laser. The readout noise of CMOS cameras is larger than that of the CCD cameras used in [11]. However, in this study this potential decrease in signal to noise ratio was compensated for by increasing the phosphorescence collection efficiency.…”
Section: Accuracy and Precision Of High-speed Phosphor Thermometrymentioning
confidence: 86%
See 2 more Smart Citations
“…Simultaneously, a UV laser is used to excite the particles, and their temperature-sensitive phosphorescence emission is recorded to determine the particle temperature applying a two-colour intensity ratio method. For micrometre-size particles, it can be shown that the particle temperature and velocity match that of the surrounding gas [1], with both Abstract Thermographic phosphor particles are seeded into the flow as tracers for simultaneous temperature and velocity measurements in fluids. Several studies using different phosphors as gas-phase tracers have been published in recent years.…”
Section: Introductionmentioning
confidence: 99%